O impacto do sistema JIT no controle de estoque logístico em barraca de feira livre e mercados de Cubatão-SP - GALVÃO, Denis do Nascimento; PEREIRA, Erik de Jesus; LEMOS, Kauê de Oliveira Carvalho; SILVA, Raphaela Santos da (181, 2025)
Este trabalho analisa a aplicação do sistema Just in Time (JIT) no controle de estoque de uma barraca de feira em Cubatão-SP, comparando também com práticas utilizadas em mercados locais. O objetivo foi entender se o JIT pode melhorar a organização, reduzir perdas de produtos perecíveis e contribuir para o aumento da eficiência e da lucratividade em pequenos comércios. A pesquisa combinou estudo teórico com entrevistas e levantamento de dados em campo. Foram analisadas três hipóteses principais, todas confirmadas: o JIT ajuda a diminuir sobras, pode ter efeitos diferentes dependendo da estrutura do negócio, e sua adoção tende a melhorar a percepção de qualidade por parte dos clientes. Mesmo sem uso de tecnologia avançada, muitos feirantes já aplicam o JIT de forma prática no dia a dia, com base na observação da demanda. Já os mercados utilizam sistemas automatizados que também seguem essa lógica. O estudo conclui que, com adaptações, o JIT é viável em pequenos negócios e pode ser uma alternativa simples e eficiente para melhorar o controle de estoque e a experiência do consumidor.

This research aims to analyze the logistical challenges faced by small e-commerce businesses, particularly microentrepreneurs in Cubatão, due to the lack of implementation of third-party fulfillment solutions. The absence of this logistical model directly impacts the operations of these businesses, resulting in high operational costs, difficulties in inventory management, delayed deliveries, and limited scalability. Due to the lack of third-party fulfillment, these entrepreneurs struggle to scale their operations effectively. Without access to an optimized logistical structure, they face challenges such as managing internal tasks, increased risk of operational errors, and difficulty offering competitive delivery times. Additionally, managing processes like storage, order picking, and shipping requires significant financial and human resources, making it difficult to compete with larger companies that already use advanced logistics solutions. The study also highlights that adopting third-party fulfillment could reduce costs, improve inventory management efficiency, and speed up delivery times, enhancing customer satisfaction and broadening the geographical reach of small businesses. Cubatão, with its strategic location and logistical infrastructure, is presented as an ideal city for the implementation of this solution, helping local e-commerce businesses grow and increase their competitiveness.
The impact of the JIT system on logistics stock control at free market stalls and markets in Cubatão-SP
Keywords: Logística (armazenagem); Estoques (armazenagem); Feiras-livres; Just in time; Gestão e Negócios